السرقة العلمية ومكافحتها في ظل القوانين والآليات التشريعية الصادرة من وزارة التعليم العالي والبحث العلمي - قعيد إبراهيم; دية السعيد; سعيدة عبد الكريم (University Of Eloued جامعة الوادي, 2023)
With the technological development, informatics and the information it provides on a large scale to students and researchers, many of whom fall within the forbidden through scientific plagiarism, Where this problem has raised a lot of talk and confusion within institutions of higher education and scientific research about the credibility and integrity of scientific research, And because this phenomenon has cast a shadow over the reputation and quality of scientific research, it has become necessary for the Algerian legislator to enact deterrent laws to reduce and combat scientific theft. Where the Ministry of Higher Education and Scientific Research issued several strict laws with the aim of addressing this negative phenomenon
Scientific theft and combating it in light of the issued laws and legislative mechanisms From the Ministry of Higher Education and Scientific Research
مداخلة
Keywords: السرقة العلمية; البحث العلمي; الأمانة العلمية; Scientific plagiarism; scientific research; scientific honesty